GRAMMAR AS COMMUNICATION: A DISCOURSE GRAMMAR OF DEIXIS - Drissia Chouit (Universitas PGRI Madiun, 2021)
This research article examines the micro-system THIS/THAT in contemporary English within the theoretical framework of Metaoperational Grammar. It proposes a new approach to bring into light how this pair functions, giving due account to the importance of the context and the communication goals that determine the selection of one of these operators in a given communication act. It aims, therefore, to bridge the gap between